Human Capital, Trade, Foreign Direct Investment and Economic Growth in Nigeria: What Causes What? - Omoyeni, Akinwale Foluso (2008)
This study investigates the long-run relationship between human capital, trade, FDI and economic growth in Nigeria for the period 1970-2006. The economic situation of the country has been quite sluggish over the years. Despite governmental efforts and policies to effect changes in the economy, the situation still looks blink. Although several major changes have been noticed in the economic situation of the country in recent years, the need for sustained economic growth on the long-run is still essential for the country. This study thus intends to determine the long-run effect of these macroeconomic variables on economic growth in Nigeria. The Eviews 6.0 software would be used to run the unit root tests, cointegration analysis test and the granger causality tests performed under the Vector Error Correction model (VECM). Empirical results of this study reveal that there is a long-run relationship between human capital, trade, FDI and economic growth in Nigeria. Although no significant short-run causality was discovered, the results seem to support the export-led growth hypothesis for Nigeria and also showed that FDI increased trade in the country. In addition, primary school education proved significant while secondary school education was not significant. This suggests that basic education is needed in the country to advance the course of economic growth. Moreover, primary school education and domestic investment served as inducing factors for the inflow of FDI into the country.